2019
DOI: 10.3802/jgo.2019.30.e88
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1/2a, dose-escalation, safety and preliminary efficacy study of oral therapeutic vaccine in subjects with cervical intraepithelial neoplasia 3

Abstract: ObjectivePersistent infection of HPV increases the chance of carcinoma in situ of cervix through stages of cervical intraepithelial neoplasia (CIN) 1, 2, and 3, and finally progresses into cervical cancer. We aimed to explore the safety and efficacy of BLS-M07 which is orally administered agent expressing human papillomavirus (HPV) 16 E7 antigen on the surface of Lactobacillus casei in patients with CIN 3.MethodsPatients with CIN 3 were recruited in our clinical trial. Reid Colposcopic Index (RCI) grading and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
(24 reference statements)
1
20
0
Order By: Relevance
“…Also, previous data, supporting the data published by Kawana et al, revealed that L. lactis vaccine, as for L. casei, can induce a systemic cell-mediated immunity which is weaker than mucosal cell-mediated immunity in the cervix and at mucosal inductive sites [49,50]. In agreement with reports by Iranian scientists regarding prophylactic and therapeutic role of recombinant L. lactis to fight against HPV-16, Korean researchers emphasized that oral immunization with L. casei vaccine harboring a modified HPV-16 E7 antigen (BLS-M07) can induce protective humoral immune responses via generating HPV-16 E7-specific IgG plasma antibody [52]. However, one of the most important limitations of this study was that they did not describe the precise mechanism of their vaccine for induction systemic and intestinal mucosa immunity.…”
Section: Clinical Trial Studies Of Hpv Vaccine Based On Labsupporting
confidence: 64%
See 1 more Smart Citation
“…Also, previous data, supporting the data published by Kawana et al, revealed that L. lactis vaccine, as for L. casei, can induce a systemic cell-mediated immunity which is weaker than mucosal cell-mediated immunity in the cervix and at mucosal inductive sites [49,50]. In agreement with reports by Iranian scientists regarding prophylactic and therapeutic role of recombinant L. lactis to fight against HPV-16, Korean researchers emphasized that oral immunization with L. casei vaccine harboring a modified HPV-16 E7 antigen (BLS-M07) can induce protective humoral immune responses via generating HPV-16 E7-specific IgG plasma antibody [52]. However, one of the most important limitations of this study was that they did not describe the precise mechanism of their vaccine for induction systemic and intestinal mucosa immunity.…”
Section: Clinical Trial Studies Of Hpv Vaccine Based On Labsupporting
confidence: 64%
“…To address these shortcomings, in recent years, the next generations of HPV vaccines including LAB-based HPV vaccines have been developed and reached the clinical trial studies. Their results indicated that this type of vaccines can elicit both potent humoral and mucosal immune responses against E6 and E7 transforming proteins [49][50][51][52][53]. Data from preclinical studies [20,35] supported the results of phase I clinical trials of Iranian researchers and reported that L. lactis vaccines could produce HPV-16 specific serum-IgG and vaginal-IgA antibodies, along with CTL response in PBMCs and vaginal discharge of sexually active healthy females.…”
Section: Clinical Trial Studies Of Hpv Vaccine Based On Labmentioning
confidence: 77%
“…Three human clinical trials in support of these pre-clinical findings were launched, in which oral immunization of recombinant L. lactis and L. casei carrying HPV-16 antigens induced high levels of specific serum IgG and vaginal IgA in volunteers who completed the vaccination schedules [ 27 , 44 , 45 ]. Interestingly, oral administration in mice of L. acidophilus carrying Gag antigen from human immunodeficiency virus 1 (HIV-1) [ 46 ] or protein HA1 from highly pathogenic avian influenza (HPAI) virus (H5N1) [ 22 ] could only stimulate local sIgA production in the digestive tract, while expression of protein HA1 of HPAI virus by recombinant L. delbrueckii subsp.…”
Section: Recombinant Probiotics As Inducers Of Humoral Immune Responsesmentioning
confidence: 99%
“…There were no grade 3 or 4 treatment-related adverse events or deaths observed among the 19 patients enrolled with CIN3. Importantly, not only did vaccination induce protective humoral immunity, but in phase 2a, six of eight subjects (75%) were cured at 16 weeks' follow-up [10]. This contrasts favorably with what is observed in clinical practice during which time regression rates of 25% may require up to 1 year or even longer.…”
mentioning
confidence: 99%
“…In the September 2019 issue of the Journal of Gynecologic Oncology , Park and colleagues [10] have reported data from a phase 1/2a dose-escalation study of BLS-M07 to treat CIN3. The vaccine is novel and is orally administered five times each week (on weeks 1, 2, 4, and 8) at a dose of 1,000 mg. By embedding the HPV 16 E7 antigen on the surface of the Lactobacillus casei vaccine construct, the investigators were able to monitor disease regression using the Reid Colposcopic Index grading system and measure serum HPV 16 E7 antibody production.…”
mentioning
confidence: 99%